Nostalgia - Rodrigues, Áurea (2022)
Nostalgia is defined as ‘a positively balanced complex feeling, emotion or mood produced by reflection on things (objects, persons, experi- ences, ideas) associated with the past’ (Holak and Havlena, 1998, p. 218). Nostalgia is differ- ent from other ways of remembering, since it is based on positive memories that individuals have experienced directly or indirectly (Holak and Havlena, 1998). The definition of nostalgia has evolved through time, and context has been studied in diverse areas of knowledge such as marketing, consumer behaviour, psychology, sociology and leisure, and seems particularly appropriate within tourism and tourist behav- iour studies (Rodrigues, 2012).